The Effect of Open Corner Care Towards Reducing The Risk of Infection in Newborn Babies at Grandmed Lubuk Pakam Hospital In 2020 - Karokaro, Tati Murni (Universitas Aisyah Pringsewu, 2020)
The purpose of this study was to determine the reduction in the risk of infection before and after open umbilical cord care for newborns at Grandmed Lubuk Pakam Hospital in 2020. This research method was quantitative with a pre-experimental research design in the form of an experimental design, namely one group pretest-posttest design, this research was conducted at Grandmed Lubuk Pakam Hospital. The results of this study are: most of the respondents before the open umbilical cord care was performed and after the open umbilical cord treatment was carried out in respondents with the risk of infection being no infection as many as 21 respondents or 70% and infection as many as 9 . By using the Wilcoxon test, the result is p-value = 0.000 with a value of = 0.05. Because the value of p = 0.000 less than 0.05, Ha is accepted, that is, there is an effect of open umbilical cord care on reducing the risk of infection in newborns at Grandmed Lubuk Pakam Hospital.